Optimal response rates in humans and rats - Freestone, David M; Balcı, Fuat; Simen, Patrick; Church, Russell M (Journal of experimental psychology. Animal learning and cognition, 2015)
The analysis of response rates has been highly influential in psychology, giving rise to many prominent theories of learning. There is, however, growing interest in explaining response rates, not as a global response to associations or value, but as a decision about how to space responses in time. Recently, researchers have shown that humans and mice can time a single response optimally; that is, in a way that maximizes reward. Here, we use the well-established differential reinforcement of low rates (DRL) timing task to show that humans and rats come close to optimizing reinforcement rate, but respond systematically faster than they should.